2017
DOI: 10.1021/acsnano.7b01760
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Gold Nanoparticles Induce Changes in Cellular and Subcellular Morphology

Abstract: Exposure of cells to colloidal nanoparticles (NPs) can have concentration-dependent harmful effects. Mostly, such effects are monitored with biochemical assays or probes from molecular biology, i.e., viability assays, gene expression profiles, etc., neglecting that the presence of NPs can also drastically affect cellular morphology. In the case of polymer-coated Au NPs, we demonstrate that upon NP internalization, cells undergo lysosomal swelling, alterations in mitochondrial morphology, disturbances in actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 81 publications
7
94
0
2
Order By: Relevance
“…Wenn dies nicht ordentlich durchgeführt wird, führt es zu falsch‐positiven Signalen, insbesondere wenn man mit Partikeln arbeitet, die eine schwache Fluoreszenz haben und in kleiner Menge dosiert werden. Die Unterscheidung von internalisierten und extrazellulären Partikeln ist möglich mit den bereits erwähnten Methoden der pH‐sensitiven Fluorophore und der Korrelation mit Immunfärbungen . In diesem Fall werden nur die Fluoreszenzen der Partikel gewertet, die lateral mit der Fluoreszenz der immungefärbten intrazellulären Organellen (Endosome/Lysosome) überlappen .…”
Section: Analyse Der Partikelaufnahme Durch Die Bestimmung Der Gemittunclassified
See 1 more Smart Citation
“…Wenn dies nicht ordentlich durchgeführt wird, führt es zu falsch‐positiven Signalen, insbesondere wenn man mit Partikeln arbeitet, die eine schwache Fluoreszenz haben und in kleiner Menge dosiert werden. Die Unterscheidung von internalisierten und extrazellulären Partikeln ist möglich mit den bereits erwähnten Methoden der pH‐sensitiven Fluorophore und der Korrelation mit Immunfärbungen . In diesem Fall werden nur die Fluoreszenzen der Partikel gewertet, die lateral mit der Fluoreszenz der immungefärbten intrazellulären Organellen (Endosome/Lysosome) überlappen .…”
Section: Analyse Der Partikelaufnahme Durch Die Bestimmung Der Gemittunclassified
“…Die Unterscheidung von internalisierten und extrazellulären Partikeln ist möglich mit den bereits erwähnten Methoden der pH‐sensitiven Fluorophore und der Korrelation mit Immunfärbungen . In diesem Fall werden nur die Fluoreszenzen der Partikel gewertet, die lateral mit der Fluoreszenz der immungefärbten intrazellulären Organellen (Endosome/Lysosome) überlappen . Der Grad der Colokalisation kann über Manders‐Koeffizienten quantifiziert werden .…”
Section: Analyse Der Partikelaufnahme Durch Die Bestimmung Der Gemittunclassified
“…Poly(methacrylic acid) HUVEC and HeLa Upon NP internalization, the lysosomal swelling, disturbances in actin and tubulin cytoskeletons, changes in mitochondrial morphology, reduction of focal adhesion contact area and number of filopodia were observed in both cell types. 20 NPs are incorporated by cells mainly via endocytic pathways and accumulated inside acidic intracellular vesicles. The decreases in cell proliferation at NP concentrations below 1 nM were found in both cells, whereas the effect of AuNPs on cell viability varied according to cell types.…”
Section: Nm (Spherical)mentioning
confidence: 99%
“…The use of AuNPs in inflammatory joint disorders, such as rheumatoid arthritis, in which new vasculature plays an important role in the disease progression, also formed a basis for the investigation of the effect of these particles on angiogenesis. Studies have shown that AuNPs can selectively inhibit the efficacy of heparin‐binding cytokines such as vascular endothelial growth factor (VEGF 165 ) and basic fibroblast growth factor (bFGF), which take an active role in the angiogenesis process . Furthermore, AuNPs of about 20 nm in size reduced VEGF‐ and bFGF‐induced endothelial cell proliferation more effectively compared to particles with size of 5 and 10 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation